Insights into the structural characteristics of four thermal dissolution extracts of a subbituminous coal by using higher-energy collisional dissociation. (15th December 2020) - Wang, Chu-Fan; Fan, Xing; Dong, Xueming; Bai, Hong-Cun; Kuznetsov, Peter N.; Liang, Peng; Liu, Zhen-Xue; Wei, Xian-Yong
Abstract: In coal chemistry, thermal dissolution (TD) is an effective processing technique to obtain soluble components from coal by using organic solvents under a certain pressure and temperature. Exploring molecular structures of the TD extracts of low-rank coal is of great importance for eco-friendly and value-added utilization in chemical industry. To well elucidate the structural information of components in coal, higher-energy collisional dissociation (HCD) specific to Orbitrap mass spectrometry was applied to analyze four TD extracts of a subbituminous coal. Alkyl chains of aromatic compounds can be removed from aromatic cores during a HCD process, allowing determination of the distribution of heteroatoms in either aromatic cores or alkyl chains. Both double bond equivalent value and carbon number of precursor ions (whole molecules) and the corresponding fragment ions (aromatic cores) obtained via a HCD process were used to evaluate the relationship between aromatic cores and alkyl chains for compounds in coal. With the increase of molecular weight, compounds in coal exhibited different distributions for aromatic cores and alkyl chains. From 200 Da to 300 Da, the increase of carbon number mainly contributed to the formation of condensed aromatic cores. However, from 300 Da to 400 Da, it was attributed to the formation of both aromatic cores and alkyl chains. In addition, heteroatom distribution index indicated that a higher TD yield of heteroatom-containing compounds would be obtained via solvents with a smaller molecular size and nitrogen-containing aromatics would be enriched by using TD solvents containing aromatic ring.